2003
DOI: 10.1051/gse:2003023
|View full text |Cite
|
Sign up to set email alerts
|

The hairless (hr) gene is involved in the congenital hypotrichosis of Valle del Belice sheep

Abstract: -Congenital hypotrichosis in mammalian species consists of partial or complete absence of hair at birth. The hairless gene is often responsible for this disorder in men, mice and rats. Recent experimental data on Valle del Belice sheep reared in Sicily for milk production, support the genetic control of the ovine hypotrichosis as a Mendelian recessive trait. The ovine hairless gene was chosen as the candidate gene involved in this disorder. Blood samples were collected from Valle del Belice sheep with the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Genomic DNA was extracted from buffy coats of nucleated cells using a salting out method (Miller et al, 1988). The PCR-SSCP (Polymerase Chain Reaction-Single Strand Conformation Polymorphism) protocol developed by Finocchiaro et al (2003a) was used to detect the genotype (CC or CT) at position 1312 bp in exon 3 of the hr gene.…”
Section: Dna Samples and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from buffy coats of nucleated cells using a salting out method (Miller et al, 1988). The PCR-SSCP (Polymerase Chain Reaction-Single Strand Conformation Polymorphism) protocol developed by Finocchiaro et al (2003a) was used to detect the genotype (CC or CT) at position 1312 bp in exon 3 of the hr gene.…”
Section: Dna Samples and Genotypingmentioning
confidence: 99%
“…In a preliminary study, Finocchiaro et al (2000) reported the genetic control of the disorder as a Mendelian recessive trait and without concomitant chromosomal rearrangements. Subsequently, Finocchiaro et al (2003a) sequenced the hr gene (GenBank Acc. No.…”
Section: Introductionmentioning
confidence: 99%
“…Marie Unna Type, 1; (OMIM:146550), which is caused by autosomal dominant mutations in the upstream ORF – U2RH [56]. Variants in HR in other species are relatively rare, but causal variants of hairless are known in sheep [17], atrichia with papular lesions is also identified in macaques [16], and, in dolphins, evolutionary loss has led to HR as a pseudogene, leading to hypotrichosis in this mammal [20]. Various other genes cause the hairless phenotypes, such as, KRT71 in the sphynx breed [9], and FOXI3 [19] and SGK3 [59,60] in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Finocchiaro et al [10] have reported segregation of the hairless (hr, Mendelian recessive) in the Valle del Belice sheep breed in Sicily. A similar gene in the Poll Dorset breed was reported much earlier by Dolling and Brooker, [8] and is characterised by a complete or partial absence of fibre at birth (hypotrichosis).…”
Section: Wool Quality Genesmentioning
confidence: 99%
“…Three mutations of this gene have been identified within an exon of the gene, and a PCR-SSCP test developed to detect the allele responsible for the hypotrichosis phenotype. Finocchiaro et al [10] also postulate that the hr gene product may play a role in cell proliferation, differentiation and apoptosis in hair follicles as well as in the interfollicular epidermis.…”
Section: Wool Quality Genesmentioning
confidence: 99%